PENERAPAN ALAT PENGERING UNTUK MENINGKATKAN PRODUKSI USAHA TERASI AWAINA KOTA LANGSA ACEH - Teuku Andi Fadlly; Sari, Nirmala; Putra, Rachmad Almi; Fajriani, Fajriani; Nila, Ida Ratna; Anda, Sabrian Tri; Fitriani, Fitriani (Universitas Negeri Surabaya, 2023)
This Community Service (PKM) provides solutions and innovations regarding the Application of Dryer Equipment to Increase the Production of Awaina Terasi Business in Langsa City, Aceh. The activity was carried out with the target of this program being the Gampong Light Terasi Business group, one of which was the Awaina Terasi Business and community groups. The main problem faced by partners is the absence of an effective, practical, and inexpensive dryer for shrimp paste during the rainy season so that production is stopped. Activities carried out for partners during service are making and training in the use of dryers for shrimp paste. The results of this activity increase the knowledge of partners and local community groups which are the Gampong Light Terasi Business group in making shrimp paste dryers that are portable, low production costs, and easy to maintain. The shrimp paste dryer will increase the production of community entrepreneurs.